Acreage Response under Varying Risk Preferences - Carlos Anthony Arnade (Journal of Agricultural and Resource Economics, 2012)
The assumption in standard expected utility model formulations that the coefficient of risk aversion is a constant is potentially unrealistic. This study takes the standard linear expected mean variance problem and replaces the coefficient of risk aversion with a function of risk aversion, allowing risk to be depicted as a constraint that farmers face. Treating output prices as stochastic, the theoretical formulation measures the impact price variability itself has on risk preferences. Acreage response elasticities are also estimated as a function of prices and price variances using U.S. county-level data for corn, soybean, and wheat producers.